Calvert Casey o la isla impossibe - Stawicka-Pirecka, Barbara (Wydawnictwo Naukowe UAM, 2003)
Casey was an emigre Cuban writer, whose works belong to a trend of the most important and original literary achievements which describe the unique character of Cuban literature of the 60’s. It was the beginning of the Revolution and the first period of the so called diaspora of Cuban writers who were leaving the island at that time as a result of oppression and acts of terror under the Castro regime directed against the Cuban intelligentsia and above all against homosexuals. The writer also spent some time in the USA, Mexico, Haiti and Geneva. He spent the most part in Rome where he committed suicide at the age of 45. His works, written under the influences of English and American literature, are at the same time one of the most original and personal expressions of «the artist outside motherland» for whom homesickness for Cuba and Havana became an obsession which defines his sensitivity of writing and the way he perceived the world.